2017
DOI: 10.1021/acs.biochem.7b00008
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Inhibition and Human Telomeric G-Quadruplex DNA Stabilization by a β-Carboline–Benzimidazole Derivative at Low Concentrations

Abstract: Guanine rich regions in DNA, which can form highly stable secondary structures, namely, G-quadruplex or G4 DNA structures, affect DNA replication and transcription. Molecules that stabilize G4 DNA have become important in recent years. In this study, G4 DNA stabilization, inhibition of telomerase, and anticancer activity of synthetic β-carboline-benzimidazole derivatives (5a, 5d, 5h, and 5r) were studied. Among them, derivatives containing a 4-methoxyphenyl ring at C and a 6-methoxy-substituted benzimidazole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Both G4s showed a positive band around 260 nm and a negative band at 240 nm, indicating the existence of a parallel G4 conformation. Upon addition of 100 µM GA, the intensity of the positive CD band of both 5′ETS and CMYC G4s decreased ( Figure 3 C) in a similar way as is described elsewhere [ 26 ]. However, the variations of the CD profile were minimal, thus proving that the overall folding of these G4s was preserved even upon ligand binding.…”
Section: Resultssupporting
confidence: 80%
“…Both G4s showed a positive band around 260 nm and a negative band at 240 nm, indicating the existence of a parallel G4 conformation. Upon addition of 100 µM GA, the intensity of the positive CD band of both 5′ETS and CMYC G4s decreased ( Figure 3 C) in a similar way as is described elsewhere [ 26 ]. However, the variations of the CD profile were minimal, thus proving that the overall folding of these G4s was preserved even upon ligand binding.…”
Section: Resultssupporting
confidence: 80%
“…Human telomerase, which also displays G4 binding, was found to partially unwind and extend the G4 structure ( 34 ). Additionally, observations that the processivity of telomerase and association with telomeres can be impaired by ligands stabilizing telomeric G4 structures both in vitro and in vivo not only marked telomeric G4 structures as potential molecular targets suitable for anticancer therapy but also further demonstrated that G4 formation is an essential component for telomere function and maintenance ( 34 38 ). Additionally, G4 also interacts with telomere-binding proteins; in S. cerevisiae , Rap1 stimulates G4 formation in vitro ( 39 , 40 ), and a functional interplay between the formation of G4 structures and Cdc13 binding has been suggested by both in vitro and in vivo experiments ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of azacyanines with tel24 were first investigated using UV-Vis and circular dichroism (CD) spectroscopy in order to quickly survey and confirm the presence of interactions between the azacyanines and tel24. Such a survey also reveals changes in the secondary structure of tel24 upon azacyanine binding and the effect of azacyanine structure on tel24 binding [25,[28][29][30][31][32][33][34][35][36][37]. Our previous structural studies using NMR have shown that one azamethyl was binding to one tel24 G-quadruplex structure between the top quartet and the A-T base pairing in the loop region.…”
Section: Determination Of Binding Using Uv-vis and CD Spectroscopymentioning
confidence: 92%
“…Benzimidazole is considered an important scaffold in the design and synthesis of pharmacophores and thus is commonly exploited [20][21][22][23]. Several studies investigating the effect of the benzimidazole scaffold on telomeric DNA and oncogene promoters such as KRAS and VEGFR that are known to fold into quadruplex structures were recently reported [24][25][26][27][28][29][30]. In addition, several reports investigating the effect of such small molecules on different cancer lines and promoting G-quadruplexes as plausible targets in cancer therapy were also published [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%